(3GdeOhfI aj Gdabg GdeGdcis - (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj,J (B191 (3g` s; (3QhGjI SMfhf Hf SYjO GdJfhMis
(3ChdgG (B:s
(3ai GdPi jahJg GdML s
(3BNQgG (B:s
(3jfJgi HcJGH GdfcGM GdKGdK Hbhdg (B: (3GdeQJO jhUi HhUGjG ajbJd Ydi QOJg s
(3GdfSNI HgG MhGTs
(3hQO GdYfhGf GdCUdi ai cX (B2 / 1644s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3QhGjIs
Keywords: (3Gdabg GdeGdcjs